Comparison of rare‐earth and hybrid‐magnet mover configurations for a permanent magnet synchronous linear motor. Issue 3 (22nd January 2021) - Liu, Xiaomei; Yu, Haitao; Gerada, David; Xu, Zeyuan; Qiu, Hongbo; Jia, Wanying; Yang, Cunxiang
Abstract: Force ripple and cost reduction are two of the main challenges in optimising the design and increasing the market uptake of permanent magnet synchronous linear motors (PMSLM). Two mover configurations are compared in depth; one made entirely from rare‐earth materials while another consisting of a hybrid (rare‐earth/ferrite) magnet layout. First, the rare‐earth PMSLM is optimised and designed. Based on the same design and simulation methods, a hybrid PM materials with structure PMSLM is then proposed, optimised and designed using NdFeB at the centre pole‐section and ferrite at the edges. The two configurations of the PMSLM and their relative merits/demerits are compared using the simulation results of the flux density distribution in the air gap, back electromotive force (EMF), and cogging force. The hybrid‐magnet structure PMLSM has a better magnetic performance, and the force ripple is reduced by around 1%. Furthermore, the magnet material cost of the hybrid‐magnet PMLSM is reduced by nearly 25% compared with the original PMLSM. Finally, a prototype of the rare‐earth and hybrid‐magnet PMSLM is manufactured and tested to validate the modelling techniques and the results.